Mutual Funds’ Performance Sensitivity to Funds’ Attributes. Case Study: Saudi Mutual Funds - Karim Soussou; Abdelwahed Omri (Financial Markets, Institutions and Risks)
This study contributes to the academic literature on faith-based mutual funds, by offering a comparative investigation of Islamic vs. conventional funds’ performance sensitivity to changes in a list of seventeen relevant funds’ attributes, all in the context of the Saudi market. The performance measures investigated are the excess return, selectivity and timing. The study took place from 2011 to 2015, with a sample of 200 Active Saudi funds, 137 Islamic and 63 conventional. Findings indicated that fund size, management fees, expense ratio cash and price-earnings ratio were irrelevant to both Islamic and conventional fund performances. In addition, we noticed similarities in both Islamic and conventional funds’ performances sensitivities towards turnover, unsystematic risk, investment target, past performance, age and management tenure. They however react differently towards a change in the price-to-book ratio. On the other hand, fund systematic risk, cashflow-to-book ratio and faith factors are exclusively relevant to Islamic funds, while fund growth and objective only affect conventional fund performance. Finally, selectivity and timing appear to be mutually exclusive, suggesting management specialization. This work appears to be the first comparative analysis of its kind. A larger, multi-regional sample, and a longer study period will provide better insights.